Sosialisasi E-Commerce dalam Meningkatkan Penjualan Produk Halal UMKM Tegal Salam Cariu - Ferdinand, Novingky; Al Farisi, Muhammad Salman; Herawati, Ermi; M. , Fauzan (Jurnal Pengabdian Masyarakat Madani, 2024)
UMKM is an abbreviation of Micro, Small and Medium Enterprises. This term refers to types of businesses that have a small or medium scale in terms of number of employees, turnover, and assets. In the digital era, micro, small and medium enterprises (MSMEs) face several obstacles that need to be overcome in order to survive and thrive in an increasingly competitive business environment. Some MSMEs may not have adequate access or knowledge about digital technology and the internet. This can make it difficult for them to adopt effective digital solutions to manage their business. The specific skills needed to take advantage of digital technologies, such as online marketing, e-commerce, web analytics, and social media management, are often lacking in MSME owners or their employees. One solution that can be put forward in overcoming this problem is to utilize digital e-commerce technology. This training is a series of activities designed to address these constraints, MSMEs need to adapt to digital changes by increasing digital literacy and leveraging existing resources to increase their reach and visibility in the online market. The method used in carrying out this activity is by holding socialization for Tegal Salam Feed UMKM in Cariu District, Bogor. The purpose of this community service activity is to provide understanding to Tegal Salam Feed MSME business actors about the importance of digital literacy in developing a business. The results of this community service activity are that Tegal Salam Feed MSME business actors can gain digital literacy and understanding by utilizing e-commerce media to develop their business.